Cloning and Expression of a Novel Leucine Dehydrogenase: Characterization and L-tert-Leucine Production - Luo, Wei; Zhu, Jing; Zhao, Yuzheng; Zhang, Huili; Yang, Xue; Liu, Yuantao; Rao, Zhiming; Yu, Xiaobin (Frontiers in Bioengineering and Biotechnology, 2020)
Among many genes encoding for amino acid dehydrogenase, a novel leucine dehydrogenase gene from Exiguobacterium sibiricum (EsiLeuDH) was isolated by using genome mining strategy. EsiLeuDH was overexpressed in Escherichia coli BL21(DE3), followed by purification and characterization. The high thermostability of the enzyme confers its half-life up to 14.7 hours at 50 °C. Furthermore, the substrate specificity shows broad spectrum, including many L-amino acids and aliphatic α-keto acids, especially some aryl α-keto acids. This enzyme coupled with recombinant formate dehydrogenase (FDH) was used to catalyze trimethylpyruvic acid (TMP) through reductive amination to generate enantiopure L-tert-leucine (L-Tle). In order to overcome the substrate inhibition effect, a fed-batch feeding strategy was adopted to transform up to 0.8 M of TMP to L-Tle, with a average conversion of 81% and L-Tle concentration of 65.6 g•L-1. This study provides a highly efficient biocatalyst for the synthesis of L-Tle and lays the foundation for large-scale production and application of chiral non-natural amino acids.